2022
DOI: 10.2471/blt.21.286650
|View full text |Cite
|
Sign up to set email alerts
|

Unequal coverage of nutrition and health interventions for women and children in seven countries

Abstract: Objective To examine inequalities and opportunity gaps in co-coverage of health and nutrition interventions in seven countries. Methods We used data from the most recent (2015–2018) demographic and health surveys of mothers with children younger than 5 years in Afghanistan ( n = 19 632), Bangladesh ( n = 5051), India ( n = 184 641), Maldives ( n = 2368), Nepal ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…This included a strong policy focus on nutrition intervention delivery through health system service delivery platforms such as well‐care contacts during and after pregnancy (i.e., antenatal care visits, skilled birth attendants, IFA supplementation, deworming, breastfeeding, and IYCF counselling), and child growth and development (i.e., management of diarrhoea, growth monitoring, immunisation, and identification and management of SAM and MAM). With regard to data gaps for the recommended nutrition interventions, we observed that India and Nepal had the most available coverage data, reported earlier (Nguyen et al, 2022 ), while Bhutan had the least. Data gaps were most common in counselling during pregnancy, interventions targeted at newborns, IYCF counselling, and identification and treatment of SAM and MAM.…”
Section: Discussionsupporting
confidence: 51%
“…This included a strong policy focus on nutrition intervention delivery through health system service delivery platforms such as well‐care contacts during and after pregnancy (i.e., antenatal care visits, skilled birth attendants, IFA supplementation, deworming, breastfeeding, and IYCF counselling), and child growth and development (i.e., management of diarrhoea, growth monitoring, immunisation, and identification and management of SAM and MAM). With regard to data gaps for the recommended nutrition interventions, we observed that India and Nepal had the most available coverage data, reported earlier (Nguyen et al, 2022 ), while Bhutan had the least. Data gaps were most common in counselling during pregnancy, interventions targeted at newborns, IYCF counselling, and identification and treatment of SAM and MAM.…”
Section: Discussionsupporting
confidence: 51%